From earth to sky: Large-scale archaeological settlement patterns in southernmost South America based on ground surveys, UAV LiDAR, and open access satellite imagery - Eidshaug, Jo Sindre P. (2024)
Large-scale archaeological surveys in coastal areas can be challenging. Factors such as remoteness, logistics, accessibility, and weather conditions can render fieldwork time-consuming and expensive in rugged archipelagic settings. Remote sensing encompasses several methods that can be used for increasing the survey area and promoting new archaeological insights. Moreover, it can be an affordable option. Google Earth (among others) collects aerial and satellite imagery from third parties and makes them freely available from anywhere in the world. In southern Tierra del Fuego, clusters of ring-shaped shell middens are conspicuous archaeological features. They are abundant in the central part of the Beagle Channel, but it has not been feasible to study their distribution across the Fuegian archipelago because we lack data from many remote areas where fieldwork is not easily conducted. Remote sensing provides a viable option for large-scale surveying due to the general visibility of these midden clusters. In this study, we establish confidence in open access satellite imagery identifications of ring-shaped middens in Tierra del Fuego based on comparisons with UAV LiDAR and conventional ground surveys, arguing that the results are appropriate for studies of large-scale trends. We provide the results from a full desk-based survey of satellite imagery provided by Google Earth, ESRI, and Microsoft Bing, covering 3000 km of coastline up to 1 km inland in southern Tierra del Fuego. Moreover, we determine the geographical distribution of ring-shaped middens and explore large-scale trends in coastal settlement patterns and landscape use—showing that ring-shaped middens are not evenly distributed across the Fuegian archipelago but strongly related to the sheltered areas of the Beagle and Murray Channels.